Denmark : Supplementary Charts and Tables. (IMF Staff Country Reports; Country Report, 1995)
This supplementary report examines selected background issues in Denmark using charts and tables. Economic growth accelerated sharply in 1994, following several years of steady but unspectacular expansion. It is projected to slow somewhat in 1995-96 but remain above potential. Unemployment, which had risen steeply during the period of subdued growth, responded slowly to the robust recovery that has been under way since the second half of 1993. However, it has been falling rapidly in recent months. Its rapid fall is projected to continue through 1996.